Pengaruh Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Yulianti, Epa; Lasmana, Andy; Melani, Maria Magdalena (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is to determine the influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR) and company size on firm value in mining companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The total population includes all mining companies listed on the Indonesia Stock Exchange (BEI) totaling 47 companies during the research period 2018, 2019, 2020, 2021 and 2022. The research sample was determined using a purposive sampling technique, totaling 9 mining companies that met certain criteria. The method applied is multiple linear regression analysis using SPSS software. The results of this research show that in partial influence on firm value, Good Corporate Governance (GCG) with managerial ownership has a positive and significant influence, while Corporate Social Responsibility (CSR) has a negative and significant influence. On the other hand, company size does not have a partially positive and significant influence on firm value. Simultaneously, it can be concluded that GCG, CSR and company size have a positive and significant influence on the value of mining companies listed on the Indonesia Stock Exchange in the 2018-2022 period.